Project: Business models to address drivers of deforestation in Peru - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 2019)
Peru is committed to reducing greenhouse gas (GHG) emissions from deforestation and agriculture, and promoting low-emissions agricultural development. To that end, it is necessary to tackle challenges related to the identification of agricultural management practices that improve productivity and reduce their contribution to GHG emissions.